Compressive Strength And Emission Temperature Of Concrete Containing Varying Percentage Of Metakaolin And Superplasticiser - Mobuli, Fittrisia Atsin; Ismail, Mohd Hanif (Recent Trends in Civil Engineering and Built Environment, 2023)
Concrete is the most widely used material in the construction industry. However, increased manufacturing of such concrete might result in increased carbon dioxide pollutants into the atmosphere, which will have a negative impact on the environment. As a consequence, additional materials / alternatives such as cement, fine aggregates, and coarse aggregates must be discovered to effectively overcome the negative impacts of the concrete manufacturing process and to make high-strength concrete using such alternative materials. Therefore this study will look at the utilization of metakaolin (MK) as a supplementary cementitious material (SCM) and superplasticiser (SP).This study will also look at the particle size analysis,workability, compressive strength, and emission temperature of high-strength concrete containing metakaolin and superplasticiser.In this study, metakaolin was used as partially replacement of cement with percentage of 5%, 10% and 15% while distinct dosage of superplasticiser which is 1.5% and 2% added as chemical admixture were being carried out with w/c 0.27.All the concrete cubes and prisms were cure in water for 7 days and 28days.The 100mmx100mmx100mm cube specimen were used to compressive strength, while the prism specimen with size 510mmx100mmx100mm tested on emission temperature concrete every hour within 7days.Based on the compressive strength, all the mix proportions were able to archive the target strength in this study which 70MPa.15%MK1.5%SP had the highest compressive strength. This is because metakaolin is pozzolanic material that can enhance the strength of concrete and also can improved cement matrix homogeneity which is help to leads to reduction in permeability.